EFFECTIVE FORMS OF ORGANIZING VISUAL ARTS ACTIVITIES IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Rakhmatova Gulobod (Web of Journals Publishing, 2025)
This article explores the effective forms of organizing visual arts activities in preschool educational institutions. It emphasizes the role of thematic lessons, play-based approaches, workshops, collaborative projects, project-based learning, digital tools, and culturally responsive methods in fostering creativity, imagination, and combinatorial skills in children. The study highlights how properly structured art activities contribute not only to artistic development but also to cognitive, emotional, and social growth.
Keywords: Preschool education, visual arts, creativity, effective organization, combinational skills, project-based learning, cultural inclusion.